Upaya Penurunan Defect karena Material Handling pada PT. X - Stefani Amelinda (Jurnal Titra, 2020)
X Company is a wood furniture manufacturer that had quality problems, which was high numbers of defect caused by worker’s error. X Company presumed these defects were caused by the worker’s handling of materials. This research aims to find the root cause of the defects caused by material handling and their solution. Observing how workers handle materials and interviewing head of production department were done for the research. Defect datas were gathered from internal inspection report and by counting the defects from failed products found in department’s output. Pareto chart was drawn to analyze which defects should be prioritized first. 5 Whys was used to analyze the root cause of the defects. Finding solutions were based from the root causes. These solutions were offered to the company’s representative to determine if they could be implemented in production area. Solutions would be improved or redesigned until they received the company’s approval.